The cost of inventory according to IAS 2 - Koliesnichenko, Anastasiia; Shen, Haojie (My University, 2023)
The conservative recordation of inventory values is important, because an overstated inventory could result in a business reporting significantly more assets than is really the case. This can be a concern when calculating the current ratio, which compares current assets to current liabilities. Lenders and creditors rely on the current ratio to evaluate the liquidity of a borrower, and so might incorrectly lend money based on an excessively high current ratio. It should be noted that there is an ongoing need to examine the value of inventory to see if its recorded cost should be reduced, due to the negative impacts of such factors as damage, spoilage, obsolescence, and reduced demand from customers. Further, writing down inventory prevents a business from carrying forward any losses for recognition in a future period. Thus, the use of net realizable value is a way to enforce the conservative recordation of inventory asset values.
Keywords: Inventory; current assets; liquidity